2018
DOI: 10.1039/c8cc03854f
|View full text |Cite
|
Sign up to set email alerts
|

In(iii)⋯In(iii) short contacts: an unnoticed metallophilic interaction?

Abstract: Based on structural evidence and a theoretical analysis, we report here the existence of close contacts between In(iii) centres in the crystals of Lewis acid-base adducts that show features of metallophilic interactions and are not present for the lighter elements of group 13.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The interaction energy of the Au I ···Au I interaction is even up to 12 kcal/mol, which is much stronger than van der Waals interactions and comparable with strong hydrogen bonds. Similar strong closed-shell interactions are also found in some other transition metals such as Cu I , Ag I , Hg II , and Au III , which is a phenomenon known as metallophilicity. …”
Section: Introductionmentioning
confidence: 53%
“…The interaction energy of the Au I ···Au I interaction is even up to 12 kcal/mol, which is much stronger than van der Waals interactions and comparable with strong hydrogen bonds. Similar strong closed-shell interactions are also found in some other transition metals such as Cu I , Ag I , Hg II , and Au III , which is a phenomenon known as metallophilicity. …”
Section: Introductionmentioning
confidence: 53%
“…Upon formation of the complex, the trivalent triel atom usually suffers a large deformation, changing its planar structure to a pseudo-tetrahedral one thus changing to an sp 3 -hybridization. Recently, 'like-like' In(III)• • • In(III) interactions was studied by Echeverría [101,102] in the crystal of trimethyltriphenyl-phosphine-indium. These unprecedented metallophilic interactions have not been described for the lighter elements of group 13.…”
Section: Triel Bondsmentioning
confidence: 99%
“…On the other hand, homopolar dihydrogen bonds in alkanes behave differently depending on the substituents attached to the interacting units, going from a pure dispersion-bound system in methane to a considerable charge transfer-stabilized dimer in the case of polyhedranes. It has been also demonstrated that the silane-methane dimer, traditionally considered as a dispersion system, has a non-negligible electrostatic contribution . Moreover, the importance of orbital mixing in closed-shell interactions in metal complexes, historically attributed to dispersion forces enhanced by relativistic effects, has been recently well established. …”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a deep knowledge of the origin of a given interaction is crucial to control and eventually exploit it at the nanoscale, in crystal engineering or materials design. Especially difficult is to distinguish between the contribution of orbital mixing and electrostatic attraction in σ- and π-hole interactions because the empty orbital and the electron density hole, responsible for the latter and the former, respectively, are located at the same region of the molecule. This fact has lead, for instance, to a longlasting debate about the dipolar or orbital nature of carbonyl–carbonyl interactions in proteins and organic molecules. , Moreover, recent reports have also pointed out the possibility of having attractive interactions between atoms that are electrostatically equivalent, for which the prediction of an attraction based on the molecular electrostatic potentials is no longer useful. ,, …”
Section: Introductionmentioning
confidence: 99%